Drying of Porous Materials - Kowalski, Stefan Jan (Springer Netherlands : Imprint: Springer, 2007)
This book provides recent advances in research on drying of saturated particulates and porous materials. The present volume is based on the selected papers presented at the XI Polish Drying Symposium 2005. The selected contributions cover theoretical modeling as well as experimental research on heat and mass transfer in porous and multiphase media during drying. The comprehensiveness and profound treatment of the subject makes this book an excellent pioneering contribution to the science and technology of drying of particulate solids. Audience: These articles written by experts in the field will be of interest not only to academic and researches in porous media but also to engineers active in food processes, nanotechnology or reaction technology.